Pemahaman Hadis Eskatologi Perspektif Teori Strukturalisme: Pendekatan Mongin Ferdinand De Saussure - Sultan Gholand Astapala; Rohimin Rohimin (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: This study attempts to understand the eschatological hadiths about the signs of cessation using a structuralism theory approach, this study is very necessary to be studied because in understanding the eschatological hadiths, they are often understood literally without considering the historical and social context at the time the hadith was delivered. This study uses a library research method, namely a type of library research using a descriptive-analytical method, namely describing the structuralism theory and analyzing the eschatological hadiths about the signs of cessation using a structuralism theory approach. The eschatology of the hadith discusses the descent of the Prophet Jesus, the emergence of the Dajjal, the rising of the sun from the west, and the signs of its cessation. In the hadith of the descent of the Prophet Jesus, the redaction is explained as a signifier-signified, langueparole, as well as synchronic and diachronic understanding, with the syntagmatic and paradigmatic role of the Prophet Jesus as a savior. The hadith of the rising of the sun from the west is studied from the redaction, meaning, langue-parole, contextual interpretation, and the paradigmatic syntagmatic structure of the subject-predicate-adverb sentence. The hadith on the appearance of the Dajjal is studied in terms of signifiers, editorial and meaning, langue-parole as a reminder of faith, as well as synchronic diachronic and syntagmatic paradigmatic understanding of the Dajjal as an object.Keywords: Hadith, Eschatology, Structuralism Theory.Abstrak: Penelitian ini berusaha memahami hadis-hadis eskatologi tentang tanda-tamda kiamat dengan menggunakan pendekatan teori strukturalisme, kajian ini sangat perlu dilakukan untuk dikaji karena dalam memahami hadis eskatologi sering dipahami secara literal tanpa mempertimbangkan konteks historis dan sosial pada saat hadis disampaikan. Penelitian ini menggunakan metode penelitian kepustakaan, yaitu jenis penelitian library research dengan menggunakan metode deskriptif-analisis yakni mendeskripsikan teori strukturalisme serta menganalisis hadis-hadis eskatologi tentang tandatanda kiamat dengan menggunakan pendekatan teori strukturalisme. Hadis eskatologi membahas turunnya Nabi Isa, kemunculan Dajjal, terbitnya matahari dari barat, dan tanda kiamat. Pada hadis turunnya Nabi Isa dianalisis redaksi sebagai signifier-signified, langue-parole, serta pemahaman sinkronik dan diakronik, dengan peran sintagmatik dan paradigmatik Nabi Isa sebagai penyelamat. Hadis terbitnya matahari dari barat ditelaah dari redaksi, makna, langue-parole, interpretasi kontekstual, dan struktur sintagmatik paradigmatik kalimat subjek-predikat-keterangan. Hadis kemunculan Dajjal dikaji dari segi signifier-signified, redaksi dan makna, langue-parole sebagai peringatan keimanan, serta pemahaman sinkronik diakronik dan simbolik sintagmatik paradigmatik Dajjal sebagai objek.Kata kunci: Hadis, Eskatologi, Teori Strukturalisme.